Implementasi Akuntansi Dalam Rangka Meningkatkan Kualitas Laporan Keuangan UMKM - Jamian Purba; Dian Sulistyorini Wulandari; Rustianah Rustianah; Yurman Zega (Jurnal Kabar Masyarakat, 2024)
Micro, small, and medium enterprises (MSMEs) have an important position and function that, together with state-owned or private enterprises, carry out various businesses to achieve prosperity for the community. The function of MSMEs is to unite, direct, and develop the creative power and business power of the people, especially those with limited economic capacity so that they can participate in economic activities. Accounting information is used to assess management activities in managing assets entrusted to them (the stewardship function) and is also used as a decision-making tool by those who use it. MSMEs experience problems understanding the application of accounting in their business operations. The efforts they make are to improve the ability of their accounting personnel through training that is carried out incidentally both by related agencies and through activities carried out by universities. However, their efforts have not produced optimal results, coupled with a fairly high level of employee mutation, where employees who have been trained sometimes change workplaces. This problem is latent and occurs repeatedly, so it greatly disrupts the daily operations of MSMEs. To be able to achieve the objectives of the activity, the method used was in the form of assistance to 20 MSMEs. This assistance is carried out by providing a multimedia-based accounting simulation device to MSMEs and then explaining how to use it. This mentoring activity begins with a briefing on the use of the device. After that, monitoring the simulation device's utilization was carried out. The final activity carried out was an evaluation of the usefulness of the device in improving the ability of MSMEs to prepare financial reports.